Exploring Thematic Progression of EFL Students’ Argumentative Essays - Haji, Ghada (The Study Program of English Education of Palangka Raya University, 2024)
This paper aims to investigate the thematic progression patterns in students’ argumentative essays produced by Tunisian EFL learners. The data originated from 27 academic essays written by second year Business English students were collected, investigated and interpreted employing a qualitative approach with descriptive analysis relevant to thematic progression patterns based on the theory proposed by Bloor and Bloor (2004). The preliminary results suggested the students’ predominant use of the constant pattern which implies that they are successfully able to ensure smooth information flow in their writings. Besides, the thematic analysis revealed the presence of the linear pattern, which proved the writers’ ability to maintain the essays’ cohesion by introducing new information and making a Rheme to become the Theme of the next clause. However, the results demonstrated the low presence of the split-rheme pattern and the total absence of the derived theme in the students’ argumentative essays, which indicates their limited writing skills in creating, developing, and connecting complex clauses. This study intends to provide contributive insights that may help EFL and ESL instructors as well as curriculum designers to enhance the students’ textual coherence as well as their academic writing proficiency.